(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The study was conducted to build the union level digital database and maps of potato during 2008-09. Both primary and secondary data were used in the study. Data were collected from all blocks of four upazilas of four districts and farmers’ level. Union, upazila, district, and country level digitized maps of Bangladesh were used in the programme. GIS, GPS, and MIS related IT were used in the study. Out of total cultivable land (1,00611 ha) in four upazilas, potato cultivated area and production were 27,414 ha and 3,32,424 t, respectively. Eighteen (18) varieties of potato were cultivated in the study areas, among them 13 were HYVs and 5 were local varieties. Out of 41 HYVs of potato developed by BARI upto 2008, 13 were cultivated in the study areas. Maximum (89.7%) area of HYV potato was covered by Diamant, Cardinal, Granola and Multa. At Chandina and Gozaria, potato area was only cultivated by HYVs. Shibganj and Pirganj shared 64 and 61% potato areas, respectively under HYVs. Average potato yields of these upazilas and Gozaria were 14.34 and 24.36 t/ha, respectively, during 2008-09. Production cost and selling price were Tk. 8.73 and 11.56 per kg, respectively at the time of harvest in 2009. Benefit Cost Ratio (BCR) of potato was 1.32 and maximum was 1.37 at Pirganj. Besides adopting high yielding and hybrid varieties, management practices should be improved. It is possible to increase potato production by vertical and horizontal expression (Uddin, 2009). Keywords: Union level digital database; maps; area; production; adoption; potato DOI: 10.3329/bjar.v35i3.6452 Bangladesh J. Agril. Res. 35(3) : 453-463